The Effect of Income, Savings, Education Level, Number of Household Members, and Household Criteria (Smoker and Non-Smoker) on Household Consumption Expenditure in Sungailiat District - Nisa, Khoirun; Hidayati, Hidayati; Wahyudin, Nanang (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2022)
The purpose of this research is to analyse and determine the effect of income, savings, education level, number of household members, and household criteria (smoker and non smoker) on household consumption expenditure in Sungailiat District. This study relied on primary data from 100 household in Sungailiat District. Data analysis was performed with multiple linier regression. The results demonstrated and partially income, number of household member, and household criteria (smoker and non-smoker) had a positive and significant effect. Savings showed a negative and significant effect. Meanwhile, education level provided a positive and insignificant effect. Simultaneously income, savings, eduation level, number of household member, and household criteria (smoker and non-smoker) affected household consumption expenditure in Sungailiat District. On average, Sungailiat District residents use nearly all of their earnings on consumption. Most consumption expenditures are made to meet food needs. Household with smoker spend more money on consumption than non-smokers.